2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin induces liver lipid metabolism disorder via the ROS/AMPK/CD36 signaling pathway. (19th December 2022) - Cong, Yewen; Hong, Yujing; Wang, Dandan; Cheng, Pei; Wang, Zhisheng; Xing, Changming; Sun, Wenxing; Xu, Guangfei
Abstract: 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is widely considered as the most toxic and common carcinogen in the world. Exposure to TCDD causes liver lipid metabolism disorder and steatosis. However, the molecular mechanism of TCDD-induced liver lipid accumulation is not completely clear. Here, we found that a 5 μg/kg TCDD exposure for 3 weeks induced hepatocyte lipid deposition, increased CD36 expression, and promoted AMP-activated protein kinase (AMPK) ɑ phosphorylation in the liver of C57BL/6J mice. Furthermore, sulfo-N-succinimidyl oleate, a CD36 inhibiter, blunted TCDD-induced lipid deposition in Huh7 cells, confirming the critical role of CD36 in TCDD-induced hepatic steatosis. In terms of molecular mechanisms, we found that TCDD exposure increased reactive oxygen species (ROS) levels in Huh7 cells, which activated AMPK. Moreover, the activated AMPK upregulated CD36 expression. Therefore, we can see that the increase in CD36 expression induced by TCDD was regulated by ROS/AMPK/CD36 signaling pathway. Our results help to clarify the molecular mechanism of TCDD-induced hepatic steatosis.